Digital and Telecom : Myanmar Infrastructure Monitoring - World Bank (Washington, DC: World Bank, 2022)
Myanmar has experienced a series of total and partial internet shutdowns since the military coup in February 2021. These restrictions have varied in intensity across the country and over time, ranging from the complete shutdown of all wireless broadband services and nightly shutdowns of fixed line services between February and April 2021, followed by limited access to a whitelist of websites and services and intermittent subnational shutdowns starting in May 2021. The restrictions on internet access have had a profound impact on investments in the sector, subsequently affecting the growth of digital infrastructure and digitally enabled services in Myanmar. Internet restrictions have also had important implications on household welfare, firm operations, and growth of the digital economy in Myanmar. New regulations, market exit by private sector providers, and continued internet restrictions threaten to reverse the progress made over the last decade. Continued internet restrictions can lead to further restraint of online economic activity and closure of many young digital start-ups that rely on consistent, reliable, and widespread internet adoption to reach markets.